PERILAKU PETANI DALAM MEREDUKSI PENGGUNAAN PESTISIDA KIMIA PADA BUDIDAYA BAWANG MERAH - Tahyudin Tahyudin; Rudi Hartono; Oeng Anwarudin (Program Studi Pengembangan Masyarakat Islam (PMI) FIDIKOM, UIN Syarif Hidayatullah Jakarta, 2020)
AbstractThe use of pesticides is still fairly high.The application of Integrated Pest Management (IPM) technology proven to reduce the use of chemical pesticides. The purpose of this study aims to analyze the level of behavior of farmers in reducing the use of chemical pesticides, analyze the factors related to the behavior of farmers in reducing the use of chemical pesticides and develop alternative strategies to improve the behavior of farmers in reducing the use of chemical pesticides in onion cultivation. Determination of the research sample using cluster random sampling and obtained a sample of 62 people. Data analysis used descriptive analysis, Spearman Rank correlation analysis and Kendall's W test. The results showed that the majority of farmers 'behavior were in the medium category with a percentage of 81%. Factors related to farmers' behavior in reducing the use of chemical pesticides were land area, extension activities and support the government and strategies to improve farmers' behavior in reducing the use of chemical pesticides including conducting counseling, making demonstration plots of IPM technology implementation and holding field activities to introduce IPM technology.Keywords: behavior; chemical pesticide reduction; IPMAbstrakPenggunaan pestisida masih terbilang tinggi.Penerapan teknologi Pengendalian Hama Terpadu (PHT) terbukti dapat menurunkan penggunaan pestisida kimia. Penelitian bertujuan untuk menganalisis tingkat perilaku petani dalam mereduksi penggunaan pestisida kimia, menganalisis faktor-faktor yang berhubungan dengan perilaku petani dalam mereduksi penggunaan pestisida kimia dan menyusun alternatif strategi untuk meningkatkan perilaku petani dalam mereduksi penggunaan pestisida kimia pada budidaya bawang merah. Penentuan sampel penelitian menggunakan cluster random sampling dan diperoleh sampel sebanyak 62 orang. Analisis data menggunakan analisis deskrptif, analisis korelasi Rank Spearman dan uji Kendall’s W.Hasil Penelitian menunjukkan tingkat perilaku petani mayoritas berada pada kategori sedang dengan persentase 81%, Faktor yang berhubungan dengan perilaku petani dalam mereduksi penggunaan pestisida kimia adalah luas lahan, kegiatan penyuluhan dan dukungan pemerintah dan strategi peningkatan perilaku petani dalam mereduksi penggunaan pestisida kimia diantaranya yaitu menyelenggarakan penyuluhan, membuat petak percontohan penerapan teknologi PHT dan mengadakan kegiatan temu lapang pengenalan teknologi PHT.Kata kunci: perilaku; reduksi pestisida kimia; PHT